2018
DOI: 10.1371/journal.pone.0190045
|View full text |Cite
|
Sign up to set email alerts
|

Do systematic reviews address community healthcare professionals’ wound care uncertainties? Results from evidence mapping in wound care

Abstract: BackgroundComplex wounds such as leg and foot ulcers are common, resource intensive and have negative impacts on patients’ wellbeing. Evidence-based decision-making, substantiated by high quality evidence such as from systematic reviews, is widely advocated for improving patient care and healthcare efficiency. Consequently, we set out to classify and map the extent to which up-to-date systematic reviews containing robust evidence exist for wound care uncertainties prioritised by community-based healthcare prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…Thus, the nursing team should assume responsibility for patients safety, so that its clinical decisions be in line with the best scientific evidence available. However, there are records in the literature of failures in the nursing care process, as evidenced in previous research 10 , 16 - 17 . It is possible to mention the dissatisfaction of patients with complex surgical wounds with the lack of continuity and quality of nursing care in the management of the complex wound, particularly the lack of information about the care to be provided to the wound in post-discharge moments, conflicting pieces of information provided by different healthcare professionals and failure to comply with the frequency of exchange of dressings at home 10 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, the nursing team should assume responsibility for patients safety, so that its clinical decisions be in line with the best scientific evidence available. However, there are records in the literature of failures in the nursing care process, as evidenced in previous research 10 , 16 - 17 . It is possible to mention the dissatisfaction of patients with complex surgical wounds with the lack of continuity and quality of nursing care in the management of the complex wound, particularly the lack of information about the care to be provided to the wound in post-discharge moments, conflicting pieces of information provided by different healthcare professionals and failure to comply with the frequency of exchange of dressings at home 10 .…”
Section: Discussionmentioning
confidence: 95%
“…In this context, the management of the treatment of surgical wounds should include the identification of possible critical factors for healing so as to provide individualized care. Nursing performance has an important role in monitoring the evolution of the wound healing process in general, however, previous studies 10 , 16 - 17 have shown flaws and lack of knowledge in clinical practice, impacting the quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…Although pain is considered the fifth vital sign, the literature suggests that there is poor compliance with local pain assessment protocols . There is much uncertainty in wound care, which means decision making can be difficult, contributing to ineffective treatment and patient harm . Uncertainty can affect any health care decision, such as assessment, diagnosis, and management.…”
Section: Discussionmentioning
confidence: 99%
“…35 There is much uncertainty in wound care, which means decision making can be difficult, contributing to ineffective treatment and patient harm. 36 Uncertainty can affect any health care decision, such as assessment, diagnosis, and management. Results of numerous studies 37 over the past decades provide evidence that many nurses caring for patients in pain lack adequate information about pain management, which can also be applied to other health professionals involved in wound care.…”
Section: Discussionmentioning
confidence: 99%
“…Our priority-setting process, with considerable stakeholder engagement, in particular consumers, and using comprehensive and explicit methods compares favourably against these. With regards to outcome evaluations, Buckley [2] and Christie [7] both assessed the research activity (including systematic reviews) that had arisen subsequent to their stakeholder-derived research priorities. Compared to our evaluation, these would answer just one of the elements (Shifted priorities and/or reallocation of resources) that we report against.…”
Section: Discussionmentioning
confidence: 99%